MOLECULAR DETECTION OF NEW STREPTOMYCES SPP. FROM IRAQI OIL CONTAMINATED SOIL - A. K. Al zaidy,; A. A. Al doori,; E. H. Yousif, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
Streptomyces spp. is one of Actinomycete that produce variety of secondary metabolite (antibacterial, antifungal and anticancer product). Bacteria that used in this study was isolated from oily soil in Baghdad /Iraq. The morphological characters was gram positive, branching, spore former. The goal of this research was to find genetic polymorphisms of one bacterial isolate (assigned S1) and to assess the accurate phylogenetic distribution of this isolated based on ribosomal sequences. In this work one genomic region was amplified that covered a portion of the 16S rRNA sequences. According to the identified results, the currently investigated sample was positioned within the major phylogenetic clade of the Streptomyces albidoflavus sequences in the generated comprehensive tree. In conclusion, the present tree provided an inclusive tool for the confirmed identity of the sample under investigation As a result, the PCR-sequencing approach was used in the studied sample has presented a confirmed identity of this sample and showed the pattern of its phylogenetic distribution. This sort of observed diversity may suggest the possibility to utilize the current 16S rRNA sequences in the accurate detection and discrimination for the Streptomyces albidoflavus sequences.